PERHITUNGAN PENURUNAN UMUR TRANSFORMATOR AKIBAT PENGARUH SUHU LINGKUNGAN - Adhie Satrya Gianto; Chairul Gagarin Irianto; Darto Gianto (Website, 2015)
The normal transformer lifespan can not be ascertained due to various causes, among others, the operating / different loading and ambient temperature factors. The life expectation of transformer will be achieved if distribution transformer is operated with continuously loaded at room temperature 20 °C and winding temperature 98 °C. The transformer which is operated in Indonesia with 30 °C room temperature will decrease thecapacity of the normal lifespan to 91%. From the calculation of loading, in accordance with the characteristics of thermal obtained from the transformer type test, although the transformer is designed to operate at an ambient temperature of 20 °C but operated at a temperature of about 30 °C, it turns out there are several types of transformers that do not decrease the capacity of the lifetime. Transformer number 2, 3, 4, and 5 despite decrease the capacity can still be operated above 91%. So in order to obtain optimal loading, we must know the thermal characteristics of each transformer that is obtained from the results of thetype test.Umur normal transformator tidak dapat dipastikan karena bemacam-macam penyebab antara lain pada faktor operasi/pembebanan yang berbeda dan kondisi suhu sekitar. Umur harap transformator akan tercapai bila transformator distribusi dioperasikan dengan pembebanan yang kontinu pada suhu ruang 20 °C dan kenaikan suhu belitan 98 °C, tetapitransformator yang dioperasikan di Indonesia yang mempunyai suhu ruang sekitar 30 °C akan mengalami penurunan kapasitas menjadi 91% dari umur normalnya. Dari hasil perhitungan pembebanan, sesuai dengan karakteristik termal yang didapat dari hasil uji jenis transformator, walaupun transformator tersebut dirancang untuk beroperasi pada suhu sekitar 20 °C tetapi dioperasikan pada suhu sekitar 30 °C, ternyata ada beberapa jenis transformator yang tidak mengalami penurunan kapasitas umur. Transformator nomor 2, 3, 4 dan 5 walaupun mengalami penurunan kapasitas masih dapat dioperasikan di atas 91%.Jadi untuk mendapatkan pembebanan yang optimal, harus mengetahui karakteristik termal masing–masing transformator yang didapat dari hasil uji jenis.